On the Date of Composition of Additions B and E to LXX Esther - Domazakis, Nikolaos (Journal for the study of Judaism, 2021)
Abstract Additions B and E to LXX Esther have been variously dated from the second century BCE to the first century CE . This study links the two Greek Additions, on the one hand, with Philo’s writings through the concept of the “evil-hating justice” and, on the other hand, with the historical persons and events related to the Jewish-Alexandrian conflict of 38-41 CE , and dates their composition or final redaction to the early forties of the first century CE .